2018
DOI: 10.1182/bloodadvances.2018017004
|View full text |Cite
|
Sign up to set email alerts
|

Sequential allogeneic and autologous CAR-T–cell therapy to treat an immune-compromised leukemic patient

Abstract: Key Points CAR-T–cell therapy normally requires the patient’s own healthy T cells. An allogeneic CAR-T bridging therapy could rescue lymphopenic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
1
26
0
1
Order By: Relevance
“…Two case reports have shown that the use of HCART19 cells as part of a conditioning regimen for allo-HSCT has beneficial therapeutic effects [6,7]. In another case involving the HCART19 cells, no myeloablative conditioning regimen was used, and the patient had a mild response to treatment, which is consistent with the responses we observed [5]. Several reports have found that B-ALL relapses after treatment with autologous CAR-T cells.…”
Section: To the Editorsupporting
confidence: 86%
See 1 more Smart Citation
“…Two case reports have shown that the use of HCART19 cells as part of a conditioning regimen for allo-HSCT has beneficial therapeutic effects [6,7]. In another case involving the HCART19 cells, no myeloablative conditioning regimen was used, and the patient had a mild response to treatment, which is consistent with the responses we observed [5]. Several reports have found that B-ALL relapses after treatment with autologous CAR-T cells.…”
Section: To the Editorsupporting
confidence: 86%
“…Patient 6 exhibited subcutaneous tissue infiltration in the right upper limb, and the infiltrating lesion was alleviated after HCART19 cell infusion. Three cases have been reported to have received HCART19 cells before allo-HSCT [5][6][7]. Two case reports have shown that the use of HCART19 cells as part of a conditioning regimen for allo-HSCT has beneficial therapeutic effects [6,7].…”
Section: To the Editormentioning
confidence: 99%
“…First-generation CAR-T cells, which contain a CAR construct with only CD3ζ in the intracellular domain, showed limited antitumor efficacy in clinical trials 16,256 , mainly due to the lack of costimulatory molecules that are essential for T cell responses to antigens 257,258 . In fact, the intracellular signal transduction domain always includes the indispensable CD3ζ chain, which contains immunoreceptor tyrosine-based activation motifs (ITAMs) that function in signal transduction 259 , and one or more intracellular costimulatory molecules, such as CD28, 4-1BB (CD137), or CD27, to transmit activation signals 180,[260][261][262][263][264][265][266][267][268][269][270] . In terms of the intracellular signal domain, CARs have evolved from the first to the fourth generation.…”
Section: Intracellular Domainmentioning
confidence: 99%
“…Adding CD27 to the second-generation CAR construct increased T cell expansion, BCL-X L upregulation, and IFN-γ production, and the resulting cells showed comparable in vivo efficacy compared with CD28ζ and 4-1BBζ CAR-T cells 308 . In addition, clinical data demonstrated that CD28-CD27-CD3ζ CAR-T cells were safe when infused to treat leukemia 262,308 . The intracellular domain of NKG2D, either individually or in combination with CD28/4-1BB domains, enhanced many properties of CAR-T cells, including the secretion of IFN-γ, TNF-α, and GM-CSF, and improved antitumor efficacy in vivo [309][310][311][312][313] .…”
Section: Intracellular Domainmentioning
confidence: 99%
“…К настоящему времени стало более очевидным, что подходы к лечению ОЛ с прогностически неблагоприятными кариотипами должны стать не только индивидуализированными, но и максимально щадящими. По-видимому, не последнее место в них должно быть отведено использованию менее повреждающих геном таргетных гипометилирующих препаратов и гистондеацетилирующих агентов, полностью ретиноевой кислоты, ингибиторов контрольных точек и многого другого [61][62][63]. Не менее очевидно и то, что некоторые малоперспективные с точки зрения длительной выживаемости после аллоТГСК больные должны переводиться на поддерживающую паллиативную терапию, причем достаточно рано.…”
Section: заключениеunclassified